Avulsion Fractures of the Femoral Head: Internal Fixation Using a Ventral Approach to the Hip Joint - L’Eplattenier, H. F.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Avulsion fractures of the femoral head are encountered in conjunction with craniodorsal luxations of the hip joint and cannot be treated conservatively without risking either reluxation of the joint or considerable cartilage damage resulting in degenerative joint disease. Fixation of the fragment is possible by inserting a Kirschner wire and a lag screw from the articular surface, making sure the implants are well countersunk. A ventromedial approach to the hip joint allows good visibility of the joint surface and easy reduction of the fracture without severing the round ligament. The surgical technique described was used on three cases and combines a ventromedial approach to the hip joint with fixation of the fracture with a Kirschner wire and a lag screw inserted from the joint surface, and has the advantages of enabling good reconstruction of the joint surface as well as maintaining postoperative joint stability. Both these factors considerably reduce the development of degenerative joint disease and improve the prognosis for recovery of full limb function.A surgical technique for treatment of avulsion fractures of the femoral head is described. It combines a ventromedial approach to the hip joint with fixation of the fracture with a Kirschner wire and a lag screw inserted from the joint surface.
Keywords: Fracture of the femoral head; articular lag screw; mini implants